2007
DOI: 10.1104/pp.107.104646
|View full text |Cite
|
Sign up to set email alerts
|

Heat Suppresses Activation of an Auxin-Responsive Promoter in Cultured Guard Cell Protoplasts of Tree Tobacco

Abstract: Cultured guard cell protoplasts (GCP) of tree tobacco (Nicotiana glauca) comprise a novel system for investigating the cell signaling mechanisms that lead to acquired thermotolerance and thermoinhibition. At 32°C in a medium containing an auxin (1-naphthaleneacetic acid [NAA]) and a cytokinin (6-benzylaminopurine), GCP expand, regenerate cell walls, dedifferentiate, and divide. At 38°C, GCP acquire thermotolerance within 24 h, but their expansion is limited and they neither regenerate walls nor reenter the cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 47 publications
(97 reference statements)
0
10
0
Order By: Relevance
“…Furthermore, indole-3-acetic acid acts in a fluctuating background of signaling molecules that are being metabolized, sequestered, and transported and for which there are tissue-specific receptors, signaling pathways, and modulators as well as redundant signaling systems. As one example, acting through a mitogen-activated protein kinase cascade, H 2 O 2 can prevent auxinresponsive gene expression in Arabidopsis and tobacco mesophyll protoplasts (Kovtun et al, 1998(Kovtun et al, , 2000, although our earlier studies provided no evidence for the involvement of H 2 O 2 in suppressed auxin signaling during sustained heat stress in cultured GCPs (Dong et al, 2007).…”
Section: Discussionmentioning
confidence: 72%
See 4 more Smart Citations
“…Furthermore, indole-3-acetic acid acts in a fluctuating background of signaling molecules that are being metabolized, sequestered, and transported and for which there are tissue-specific receptors, signaling pathways, and modulators as well as redundant signaling systems. As one example, acting through a mitogen-activated protein kinase cascade, H 2 O 2 can prevent auxinresponsive gene expression in Arabidopsis and tobacco mesophyll protoplasts (Kovtun et al, 1998(Kovtun et al, , 2000, although our earlier studies provided no evidence for the involvement of H 2 O 2 in suppressed auxin signaling during sustained heat stress in cultured GCPs (Dong et al, 2007).…”
Section: Discussionmentioning
confidence: 72%
“…Thus, both heat and L-NMMA suppress auxin-responsive transgene expression in reporter-transformed GCPs ( Fig. 6; Table I; Dong et al, 2007), suggesting that many of the inhibitory phenomena observed under both treatments are likely due to failed NO-dependent auxin signaling.…”
Section: L-nmma Reduces Shoot Growth and Prevents Lateral Root Develomentioning
confidence: 92%
See 3 more Smart Citations